Interplay between MAPK signaling pathway and autophagy in skin aging: mechanistic insights and therapeutic implications - Liu, Xu; Chen, Bo; Liu, Xuefeng; Zhang, Xiaoqing; Wu, Jingdong (Frontiers in Cell and Developmental Biology, 2025)
Skin aging manifests as structural degradation, functional decline, and heightened disease susceptibility. Central to this process is the overactivation of the mitogen-activated protein kinase (MAPK) signaling pathway triggered by reactive oxygen species (ROS). Autophagy, a lysosomal degradation mechanism essential for maintaining cellular homeostasis, demonstrates context-dependent duality in skin aging by mediating cytoprotective effects and stress-induced dysfunction. Emerging evidence highlights that the interplay between MAPK signaling and autophagy critically modulates skin aging progression. Despite its therapeutic potential, the lack of effective targeting strategies severely hinders clinical translation. Therefore, this review synthesizes current evidence on MAPK–autophagy interplay across key cutaneous cell populations, namely, keratinocytes, fibroblasts, and melanocytes (including melanoma), revealing cell-type-specific regulatory networks that influence skin aging. Subsequently, we explore the therapeutic potential of natural bioactive compounds targeting this interplay to accelerate the translation of evidence into the progression of strategies for combating skin aging.